The Effect Of Medical And Non-Medical Service Quality On Patient Satisfaction Based On Patient Cognition At XYZ Hospital Jakarta - Gading, Siska Tamara; Berlianto, Margaretha Pink (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Patient satisfaction not only reflects their personal experiences, but also becomes a very important indicator for health care providers to reach the extent to which patients' needs, expectations, and preferences are met during the treatment process. This study aims to analyze the effect of medical and non-medical service quality on patient satisfaction. The respondents were 185 patients of XYZ Hospital. The data analysis method used descriptive analysis and PLS-SEM. The results showed that patient cognition, trust, personnel quality, social responsibility had a positive effect on patient satisfaction. While other factors such as medical service procedures, administrative practices, hospital image, safety, infrastructure did not affect patient satisfaction. Hospital management is advised to improve the image of the hospital by carrying out various activities such as blood donation, counseling related to various diseases, visiting surrounding areas for disease prevention socialization, advertising digitally to form a positive image in the community. Further research can be done by increasing the population in other XYZ hospitals in the Jakarta area and limiting between BPJS and non-BPJS patients.